Blood clot contraction differentially modulates internal and external fibrinolysis. (6th February 2019) - Tutwiler, Valerie; Peshkova, Alina D.; Le Minh, Giang; Zaitsev, Sergei; Litvinov, Rustem I.; Cines, Douglas B.; Weisel, John W.
Abstract : Essentials Clot contraction influences the rate of fibrinolysis in vitro . Internal fibrinolysis is enhanced ∼2‐fold in contracted vs. uncontracted blood clots. External fibrinolysis is ∼4‐fold slower in contracted vs. uncontracted blood clots. Contraction can modulate lytic resistance and potentially the clinical outcome of thrombosis. Summary: Background: Fibrinolysis involves dissolution of polymeric fibrin networks that is required to restore blood flow through vessels obstructed by thrombi. The efficiency of lysis depends in part on the susceptibility of fibrin to enzymatic digestion, which is governed by the structure and spatial organization of fibrin fibers. How platelet‐driven clot contraction affects the efficacy of fibrinolysis has received relatively little study. Objective: Here, we examined the effects of clot contraction on the rate of internal fibrinolysis emanating from within the clot to simulate (patho)physiological conditions and external fibrinolysis initiated from the clot exterior to simulate therapeutic thrombolysis. Methods: Clot contraction was prevented by inhibiting platelet myosin IIa activity, actin polymerization or platelet‐fibrin(ogen) binding. Internal fibrinolysis was measured by optical tracking of clot size. External fibrinolysis was determined by the release of radioactive fibrin degradation products. Results and Conclusions: Clot contraction enhanced the rate of internal fibrinolysis ∼2‐fold. In contrast, external fibrinolysis was ~4‐fold slower in contracted clots. This dichotomy in the susceptibility of contracted and uncontracted clots to internal vs. external lysis suggests that the rate of lysis is dependent upon the interplay between accessibility of fibrin fibers to fibrinolytic agents, including clot permeability, and the spatial proximity of the fibrin fibers that modulate the effects of the fibrinolytic enzymes. Understanding how compaction of blood clots influences clot lysis might have important implications for prevention and treatment of thrombotic disorders.